Cover Picture: Inter‐ and intra‐tumor heterogeneity of SMAD4 loss in head and neck squamous cell carcinomas (Mol Carcinog 58/2019). Issue 5 (25th April 2019) - Hernandez, Ariel L.; Wang, Ying; Somerset, Hilary L.; Keysar, Stephen B.; Aisner, Dara L.; Marshall, Carrie; Bowles, Daniel W.; Karam, Sana D.; Raben, David; Jimeno, Antonio; Varella‐Garcia, Marileila; Wang, Xiao‐Jing
Abstract : Cover Caption : The cover image is based on the Research Article Inter‐ and intra‐tumor heterogeneity of SMAD4 loss in head and neck squamous cell carcinomas by Ariel L. Hernandez et al., DOI 10.1002/mc.22958 .